Time factor in critical modes of radio electronic system functioning (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2018)
Introduction. At the present stage of the development of technical systems, it is important to predict their development, quality, and process characteristics. This also applies to radio electronic systems. Sufficiently unfavorable situations for the functioning of radio electronic systems arise in the context of information conflicts, when it becomes necessary to predict the consequences of information loss or the effect of deliberate interference on the capabilities of radio electronic systems. In critical situations the time factor plays a significant role. On the one hand, information that comes with a delay and loses its relevance. From another point of view, it is necessary to carry out the assigned task within the prescribed time. Thus, the task of determining time indicators of the functioning of radio electronic systems in critical regimes remains urgent and requires further research. Problem statement. Take into account that the effectiveness of the radio electronic systems functioning can be estimated by the performing the task probability. In the process of information flow this probability increases and asymptotically come close to one. In critical modes of operation due to the uncertainty and unpredictability of emerging situations the processing time of information increases. Thus the available information which is perceived by the system is different from the information that is provided by the regular mode. It is necessary to find out the influence of time on processing information on the regularity of the change in the probability of accomplishing the task. It is necessary to estimate the radio electronic operation time, which is necessary to perform the task. It is necessary to set restrictions on the processing time of information and to clarify the requirements for the main parameters that characterize the operation of radio electronic systems in critical modes. From a practical point of view it is necessary to compare real and potential indicators of radio electronic systems and to provide for the possibility of predicting the consequences of their functioning critical modes. Results. On the basis of the informational approach to the analysis of processes in radio electronic systems, the main relations regarding the necessary time of their work and the restrictions on the information delay time are established. Typical situations of critical operating modes of radio electronic systems and the effect of false or lost information on their qualitative characteristics are analyzed. Indicators of a systems operation stable mode are defined. System information analysis of processes using typical forecasting models and the method of analogies is carried out. The effectiveness of the radio electronic systems depends on the amount and value of information that comes to them in the process of functioning. Taking into account the peculiarities of the work of the radio electronic systems In critical operating modes, we will consider useful information and misleading or lost information. Analysis of the work of systems with feedback in the conditions of information delay, allowed to set limits on the permissible delay time, determine the efficiency and the required operating time of the systems. For systems with information losses in the information conflict context in conditions of information capacities increasing and delaying the reaction of one of the parties to the conflict the following indicators are established: real and potential systems efficiency; limitations on the possible efficiency of systems; admissible delay time of reaction by one of the parties to the conflict; necessary time for the performance of the assigned functional task. Conclusions. The obtained results show that in critical modes of the functioning of radio electronic systems, the factor influences both the radio electronic systems performance indicators and their potential capabilities. For information systems that extract information, it became possible to take into account the time that is necessary for processing information, use a typical predictive model for the regularity of increasing the information amount and determine the efficiency and necessary time of the system operating. These results can be used in the process of the radio electronic systems modernization and at the initial stage of radio electronic systems designing.